The Ainu and Japanese Settler Colonialism - Roellinghoff, Michael (Oxford University Press, 2024)
The Ainu people are Indigenous to Hokkaido (Japan’s northernmost island in the early 21st century), the Russian-administered island of Sakhalin, and the adjacent Kuril archipelago. The Ainu traditionally refer to these lands as Ainu Mosir (meaning “the land of the people”). In the early 21st century, an increasing number of Ainu refer to Hokkaido itself as Yaun Mosir (roughly “the land of land”). Long neighbors with the Japanese, they historically resided as far south as Honshu and as far north as Kamchatka. As of 2023, most Ainu are concentrated in southern Hokkaido and the Tokyo metropolitan area. During the Tokugawa period (1603–1867), the Matsumae Domain maintained a deeply exploitative, if not outright colonialistic, relationship with Ainu groups across Hokkaido (then known in Japanese as Ezo). Nevertheless, Tokugawa leaders explicitly recognized Ainu territorial sovereignty and political formations. Following the Japanese annexation of Hokkaido in 1869, however, the Westernizing Meiji state (1868–1912) adopted settler colonial practices in Hokkaido that closely resembled those of the United States, the British Empire, and the Russian Empire. Declaring Ainu territories across Hokkaido terra nullius (empty or ownerless land), the Kaitakushi (the Japanese Colonial Office) and successive Hokkaido-based prefectural governments disregarded Ainu sovereignty entirely and engaged in a zero-sum colonization program, dispossessing the Ainu of their unceded land, waters, and resources. While this led to deadly waves of famine and epidemic disease in Ainu communities in the late 19th and early 20th centuries, many resisted. This ranged from physical confrontations with colonial agents to large-scale peaceful protests. Amid widespread social Darwinist-inflected narratives of the Ainu as a self-destructively inferior race, in 1899, the Meiji government passed the so-called Hokkaido Former Aborigine Protection Act (Hokkaidō kyūdojin hogo-hō), rendering the Ainu wards of the state. In the 21st century, the legacies of the ...